The hyperparathyroidism-jaw tumour syndrome in a Portuguese kindred. - Cavaco, B; Barros, L; Pannett, A; Ruas, L; Carvalheiro, M; Ruas, M; Krausz, T; Santos, M; Sobrinho, L; Leite, V; Thakker, R (2001)
The hyperparathyroidism-jaw tumour (HPT-JT) syndrome is an autosomal dominant disease characterized by the occurrence of parathyroid tumours and fibro-osseous tumours of the jaw bones. Some HPT-JT patients may also develop renal abnormalities, which include Wilms' tumours, hamartomas and polycystic disease. The HPT-JT gene has been mapped to chromosome 1q25-q31, and we report the clinical and genetic findings in a kindred from central Portugal. HPT-JT was observed in six members from three generations; all had primary hyperparathyroidism (five had parathyroid adenomas, one a parathyroid carcinoma). Ossifying jaw fibromas affecting the maxilla and/or mandible were observed in 5/6. Renal cysts (<2.5 cm) were observed in four. Genetic studies using 18 polymorphic loci from chromosome 1q25-q31, together with leukocyte DNA from 11 family members and tumour DNA from three parathyroids (two adenomas and one carcinoma), revealed loss of tumour heterozygosity in the parathyroid carcinoma only, and the retained haplotype was found to cosegregate with the disease in the six affected members. A new Portuguese kindred with the HPT-JT syndrome that maps to chromosome 1q25-q31 has been identified, and these findings will help in the further characterization of this inherited disorder.